Process for the production of hydrolysis-resistant tpu films

CN122956688APending Publication Date: 2026-10-23CHANG TAI CHEM HUIZHOU CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610860829.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-15
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]基于此,有必要针对现有的TPU膜耐水性不足的技术问题,提供一种耐水解TPU薄膜制备工艺

Benefits of technology

[0015]上述的耐水解TPU薄膜制备工艺通过将聚碳化二亚胺预先与聚醚型TPU共混造粒制成功能母粒,实现了高分子量抗水解剂在基体中的原位均匀锚定,既杜绝了常规小分子添加剂在高温加工及后续湿热服役过程中的挥发与迁移析出问题,又借助其长效捕获羧基的能力,从根本上阻断了TPU酸催化自水解链式反应的发生。其次,阶梯式升温干燥工艺将物料含水率强制压至002%以下,最大限度抑制了熔融挤出阶段因微量水分引发的热剪切降解,确保分子链初始端基羧基含量处于极低水平,大幅减轻了抗水解剂的初始消耗负担。再者,低温熔融挤出配合急冷及定向拉伸工艺,一方面通过骤冷形成细密微晶结构,减少水汽渗透的非晶区自由体积;另一方面利用单向拉伸诱导硬段分子链沿拉伸方向高度取向排列,在薄膜厚度方向构建起长程有序的物理阻隔屏障,显著降低了水汽在薄膜内部的扩散速率与水蒸气透过率。最后,热定型后的恒温熟化处理为抗水解功能成分与残余微量羧基提供了充分的固相反应窗口,促使薄膜内部微观结构趋于热力学稳定,彻底释放加工内应力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of preparation process of hydrolysis-resistant TPU film, which includes the following steps: hydrolysis-resistant functional master batch is prepared by blending and granulating polycarbodiimide and polyether TPU in advance;The moisture content of the material is dried to below 0.02% using a stepwise heating process;Melt extrusion casting film under low temperature conditions of 165℃-185℃;The molten film is rapidly cooled at 15℃ and combined with longitudinal unidirectional stretching to build a dense oriented structure;Finally, heat setting and constant temperature curing treatment are carried out.The application uses in-situ chemical capture of acid end group mechanism and physical stretching induced crystallization barrier mechanism to completely block the acid catalyzed self-hydrolysis process of TPU.The tensile strength retention rate of the obtained film can reach more than 85% after aging at 85℃ / 85%RH for 1000 hours, and it also has low swelling and low precipitation characteristics, especially suitable for car cover protection film and outdoor high durability composite material fields that are in contact with humid and hot environment for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of TPU film preparation technology, and in particular to a process for preparing hydrolysis-resistant TPU films. Background Technology

[0002] Thermoplastic polyurethane elastomer (TPU) is widely used in automotive protective films, outdoor sports equipment, medical devices, and inflatable structural materials due to its combination of high elasticity from rubber and high strength from plastics, along with excellent processing performance. Based on the different soft segment structures, TPU is mainly divided into two categories: polyester-based and polyether-based. Polyester-based TPU, containing highly polar ester groups (-COO-) in its molecular chain, can form a high cohesive energy density, giving the material excellent mechanical strength, abrasion resistance, and oil resistance, making it the most widely used TPU variety in the market. However, ester groups are highly susceptible to hydrolysis and breakage in humid and hot environments or acidic and alkaline media, generating carboxylic acid end groups. Carboxylic acids have a self-catalytic accelerating effect on the hydrolysis of ester groups, resulting in polyester-based TPU films typically retaining less than 30% of their tensile strength under long-term humid and hot service conditions (such as aging tests at 85℃ / 85%RH), severely limiting its application in high-end outdoor and automotive applications. To improve the hydrolysis resistance of TPU, existing technologies typically modify it by adding anti-hydrolysis stabilizers. Commonly used anti-hydrolysis agents include monomeric carbodiimides (such as diisopropylcarbodiimide and dicyclohexylcarbodiimide) or polymeric carbodiimides. Their mechanism of action is that the functional group of carbodiimide (-N=C=N-) preferentially undergoes an addition reaction with the carboxyl group generated by hydrolysis in the system, thereby consuming the acid catalyst and blocking the autocatalytic degradation cycle.

[0003] However, these small-molecule or low-molecular-weight anti-hydrolysis agents exhibit significant volatility during the melt processing of TPU. This leads to a decrease in the actual retention of the effective ingredients, and the volatilized isocyanate byproducts can pollute the production environment and pose a threat to the health of operators. Furthermore, unreacted or excessively added free anti-hydrolysis agents tend to migrate and precipitate onto the surface of the film during long-term use. This not only causes the film surface to become sticky and reduces transparency, but also weakens the interlayer adhesion between the film and adhesives or printing inks, leading to interfacial failure of the composite structure. Summary of the Invention

[0004] Therefore, it is necessary to provide a process for preparing hydrolysis-resistant TPU films to address the technical problem of insufficient water resistance in existing TPU films.

[0005] A process for preparing a hydrolysis-resistant TPU film, comprising the following steps: S1. Masterbatch preparation: Polycarbodiimide and polyether thermoplastic polyurethane are mixed at a mass ratio of (15~25):(85~75), and then melt-blended and extruded by a twin-screw extruder to obtain hydrolysis-resistant masterbatch. S2. Material Mixing and Drying: By mass, mix 100 parts of polyether-type thermoplastic polyurethane matrix resin, 3-5 parts of the hydrolysis-resistant masterbatch obtained in step S1, 1-2 parts of hydrophobic synergist, and 0.2-0.5 parts of processing aids evenly. Then, place the mixture in a dehumidifying drying device and dry it using a stepped heating process until the moisture content of the material is below 0.02%. S3, Melt Extrusion Casting: The material dried in step S2 is fed into a single-screw casting extruder and melted and plasticized at a low temperature of 165℃~185℃ from the feeding section to the die head. The material is then extruded through the die head to form a molten film. S4. Rapid cooling and stretching: After the molten film leaves the die head, it is immediately contacted with the first cooling roller at a temperature of 13℃~17℃ for rapid cooling to form a cast base film; then the cast base film is preheated and subjected to unidirectional stretching treatment with a ratio of 1:15~1:20 in the longitudinal direction under the preheated state. S5. Post-processing: The stretched film is heat-set at 90℃~110℃ to eliminate internal stress; then it is wound up and placed in a constant temperature environment of 45℃~55℃ for 18~30 hours to cure, thus obtaining the hydrolysis-resistant TPU film.

[0006] In one embodiment, the number average molecular weight of the polycarbodiimide in step S1 is 2000~5000, the length-to-diameter ratio of the twin-screw extruder is 48:1, and the processing temperature range is 160℃~190℃.

[0007] In one embodiment, the hydrophobic synergist in step S2 is 5000-mesh ultrafine talc powder that has undergone surface pretreatment with a titanate coupling agent, and the processing aid is ethylene bis-stearamide.

[0008] In one embodiment, the stepped heating and drying process in step S2 specifically includes: drying at 80°C for 1-2 hours in the first stage; drying at 100°C for 25-35 hours in the second stage; drying at 90°C for 05-15 hours in the third stage; and the dew point temperature of the dehumidifying drying equipment is not higher than -50°C.

[0009] In one embodiment, the temperature of each section of the single-screw cast extruder in step S3 is set as follows: feeding section 165℃±5℃, compression section 175℃±5℃, metering section 180℃±5℃, flange and filter area 180℃±5℃, and die head 185℃±5℃.

[0010] In one embodiment, the filter screen combination of the single screw cast extruder in step S3 is a three-layer stacked structure of 100 mesh / 200 mesh / 100 mesh.

[0011] In one embodiment, the rapid cooling treatment of the cast base film in step S4 is completed on the surface of a cooling roller at 15°C ± 2°C, and the preheating temperature is 80°C ± 5°C.

[0012] In one embodiment, the duration of the heat setting process in step S5 is 15 to 25 seconds.

[0013] In one embodiment, after the heat setting process in step S5 and before winding, a step of corona treatment on the film surface is further included, wherein the power of the corona treatment is 7~9kW and the dyne value of the treated film surface is not less than 42mN / m.

[0014] A hydrolysis-resistant TPU film is prepared by the method described above.

[0015] The aforementioned hydrolysis-resistant TPU film preparation process achieves in-situ uniform anchoring of high molecular weight anti-hydrolysis agents in the matrix by pre-blending polycarbodiimide with polyether-type TPU to form functional masterbatches. This eliminates the volatilization and migration issues of conventional small molecule additives during high-temperature processing and subsequent humid heat service. Furthermore, by leveraging its long-term ability to capture carboxyl groups, it fundamentally blocks the occurrence of acid-catalyzed self-hydrolysis chain reactions in TPU. Secondly, the stepped heating and drying process forcibly reduces the material moisture content to below 0.02%, maximally suppressing thermal shear degradation caused by trace amounts of moisture during the melt extrusion stage. This ensures that the initial end-group carboxyl group content of the molecular chain is at an extremely low level, significantly reducing the initial consumption burden of the anti-hydrolysis agent. Furthermore, the low-temperature melt extrusion combined with rapid cooling and directional stretching processes, on the one hand, form a dense microcrystalline structure through rapid cooling, reducing the free volume of amorphous regions where water vapor permeates; on the other hand, unidirectional stretching induces the hard segment molecular chains to align highly along the stretching direction, constructing a long-range ordered physical barrier in the film thickness direction, significantly reducing the diffusion rate and water vapor permeability within the film. Finally, the isothermal curing treatment after heat setting provides a sufficient solid-phase reaction window for the anti-hydrolysis functional components and residual trace carboxyl groups, promoting the thermodynamic stability of the film's internal microstructure and completely releasing processing stress. Detailed Implementation

[0016] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described in detail below. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0017] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0018] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components, unless otherwise explicitly limited. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0019] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0020] It should be noted that when an element is referred to as being "fixed to" or "set on" another element, it can be directly on the other element or there may be an intervening element. When an element is considered to be "connected to" another element, it can be directly connected to the other element or there may be an intervening element. The terms "vertical," "horizontal," "upper," "lower," "left," "right," and similar expressions used herein are for illustrative purposes only and do not represent the only possible implementation.

[0021] This invention discloses a process for preparing a hydrolysis-resistant TPU film, which includes the following steps: S1. Masterbatch preparation: Polycarbodiimide and polyether thermoplastic polyurethane are mixed at a mass ratio of (15~25):(85~75), and then melt-blended and extruded by a twin-screw extruder to obtain hydrolysis-resistant masterbatch. S2. Material Mixing and Drying: By mass, mix 100 parts of polyether-type thermoplastic polyurethane matrix resin, 3-5 parts of the hydrolysis-resistant masterbatch obtained in step S1, 1-2 parts of hydrophobic synergist, and 0.2-0.5 parts of processing aids evenly. Then, place the mixture in a dehumidifying drying device and dry it using a stepped heating process until the moisture content of the material is below 0.02%. S3, Melt Extrusion Casting: The material dried in step S2 is fed into a single-screw casting extruder and melted and plasticized at a low temperature of 165℃~185℃ from the feeding section to the die head. The material is then extruded through the die head to form a molten film. S4. Rapid cooling and stretching: After the molten film leaves the die head, it is immediately contacted with the first cooling roller at a temperature of 13℃~17℃ for rapid cooling to form a cast base film; then the cast base film is preheated and subjected to unidirectional stretching treatment with a ratio of 1:15~1:20 in the longitudinal direction under the preheated state. S5. Post-processing: The stretched film is heat-set at 90℃~110℃ to eliminate internal stress; then it is wound up and placed in a constant temperature environment of 45℃~55℃ for 18~30 hours to cure, thus obtaining the hydrolysis-resistant TPU film.

[0022] This embodiment utilizes four synergistic effects: in-situ anchoring of high molecular weight PCDI, extreme dehumidification to eliminate processing degradation risks, micro-stretching and orientation to improve physical barrier properties, and thermal treatment to release internal stress and complete chemical repair. This allows the tensile strength retention rate of the film to be increased from <30% for conventional polyester films to ≥85% after aging at 85℃ / 85%RH for 1000 hours. This avoids the migration and precipitation of small molecule anti-hydrolysis agents under high temperature and high humidity conditions, ensuring the long-term cleanliness of the film surface and the composite adhesion performance.

[0023] Furthermore, the number-average molecular weight of the polycarbodiimide mentioned in step S1 is 2000~5000, the aspect ratio of the twin-screw extruder is 48:1, and the processing temperature range is 160℃~190℃. This embodiment limits the number-average molecular weight of PCDI to 2000~5000, ensuring sufficient end-group activity to capture acids while preventing processing volatilization due to excessively low molecular weight or uneven dispersion due to excessively high molecular weight. The use of a twin-screw extruder with an aspect ratio of 48:1 ensures sufficient plasticization and microscopic homogeneous dispersion of the high-viscosity polycarbodiimide and the TPU carrier, providing a fundamental guarantee for the uniformity of subsequent film performance.

[0024] Furthermore, the hydrophobic synergist mentioned in step S2 is 5000-mesh ultrafine talc powder pretreated with a titanate coupling agent, and the processing aid is ethylene bis-stearamide. This embodiment uses 5000-mesh ultrafine talc powder treated with a titanate coupling agent. On the one hand, the layered structure extends the water vapor permeation path; on the other hand, the titanate coupling agent enhances the interfacial bonding between the inorganic filler and the organic TPU matrix, avoiding new water absorption channels caused by interfacial debonding. The addition of ethylene bis-stearamide ensures lubrication during demolding without affecting film transparency and has no negative impact on hydrolysis resistance.

[0025] Furthermore, the stepped heating and drying process described in step S2 specifically includes: a first stage of drying at 80℃ for 1-2 hours; a second stage of drying at 100℃ for 25-35 hours; and a third stage of drying at 90℃ for 0.5-15 hours; and the dew point temperature of the dehumidifying drying equipment is not higher than -50℃. The first stage involves low-temperature pre-drying to remove surface water and prevent clumping; the second stage involves high-temperature core-depth drying to a moisture content of <0.02%; and the third stage involves heat preservation to prevent re-moistening. This drying scheme can minimize hydrolysis side reactions during processing and avoid the vicious cycle of "melt shear degradation—carboxyl group increase—autocatalytic hydrolysis" caused by trace amounts of moisture in the screw.

[0026] Furthermore, the temperatures of each section of the single-screw cast extruder described in step S3 are set as follows: feeding section 165℃±5℃, compression section 175℃±5℃, metering section 180℃±5℃, flange and filter area 180℃±5℃, and die head 185℃±5℃. Strictly controlling the maximum processing temperature around 185℃ avoids the thermo-oxidative degradation and hard segment dissociation that are easily caused by conventional TPU processing (above 210℃). The lower processing temperature reduces the formation of new carboxyl groups, effectively reducing the burden of subsequent anti-hydrolysis agent consumption.

[0027] Furthermore, the filter combination of the single-screw cast extruder described in step S3 is a three-layer stacked structure of 100 mesh / 200 mesh / 100 mesh. Using this 100 / 200 / 100 mesh filter combination can effectively intercept trace amounts of carbides or unplasticized particles that may be present in the raw material. These tiny impurities are often the starting point for moisture to preferentially attack and cause stress cracking of the film.

[0028] Furthermore, the rapid cooling treatment of the cast base film in step S4 is completed on the surface of a cooling roller at 15℃±2℃, and the preheating temperature is 80℃±5℃. Rapid cooling at 15℃ inhibits the growth of large spherulites in the TPU hard segments, forming a finer microcrystalline structure and reducing the volume of amorphous regions for water molecule diffusion. Uniaxial stretching at 80℃ induces a high degree of orientation of the molecular chains along the stretching direction. This long-range ordered structure acts like a "molecular fence" in the thickness direction, forcing water vapor molecules to take a longer path to penetrate the film, thereby reducing the water vapor transmission rate (WVTR).

[0029] Furthermore, the heat setting process described in step S5 lasts for 15 to 25 seconds. Heat setting at 100°C for 15 to 25 seconds can relax the internal stress generated by stretching while maintaining the stretching orientation effect.

[0030] Furthermore, after the heat setting treatment in step S5 and before winding, a corona treatment step is included on the film surface. The power of the corona treatment is 7~9kW, and the dyne value of the treated film surface is not less than 42mN / m. The corona treatment generates polar groups on the film surface, with a dyne value ≥42mN / m, ensuring that when used as a base film for car covers or composite fabrics, it can achieve high-strength peel adhesion with adhesives or coatings, avoiding interlayer peeling failure due to insufficient interfacial adhesion in long-term humid environments.

[0031] This invention also discloses a hydrolysis-resistant TPU film, which is prepared by the above method. The tensile strength retention, volume swelling rate, and hydrogen peroxide aging resistance of this hydrolysis-resistant TPU film are compared with existing conventional polyester TPU films, as shown in Table 1 below.

[0032] Table 1

[0033] In summary, the hydrolysis-resistant TPU film preparation process disclosed in this invention achieves in-situ uniform anchoring of high molecular weight anti-hydrolysis agents in the matrix by pre-blending polycarbodiimide with polyether-type TPU to form functional masterbatches. This not only eliminates the volatilization and migration issues of conventional small molecule additives during high-temperature processing and subsequent humid heat service, but also fundamentally blocks the occurrence of acid-catalyzed self-hydrolysis chain reactions in TPU by leveraging its long-term ability to capture carboxyl groups. Secondly, the stepped heating and drying process forcibly reduces the material moisture content to below 0.02%, maximally suppressing thermal shear degradation caused by trace amounts of moisture during the melt extrusion stage. This ensures that the initial end-group carboxyl group content of the molecular chain is at an extremely low level, significantly reducing the initial consumption burden of the anti-hydrolysis agent. Furthermore, the low-temperature melt extrusion combined with rapid cooling and directional stretching processes, on the one hand, form a dense microcrystalline structure through rapid cooling, reducing the free volume of amorphous regions where water vapor permeates; on the other hand, unidirectional stretching induces the hard segment molecular chains to align highly along the stretching direction, constructing a long-range ordered physical barrier in the film thickness direction, significantly reducing the diffusion rate and water vapor permeability within the film. Finally, the isothermal curing treatment after heat setting provides a sufficient solid-phase reaction window for the anti-hydrolysis functional components and residual trace carboxyl groups, promoting the thermodynamic stability of the film's internal microstructure and completely releasing processing stress.

[0034] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0035] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A process for preparing a hydrolysis-resistant TPU film, characterized in that, Includes the following steps: S1. Masterbatch preparation: Polycarbodiimide and polyether thermoplastic polyurethane are mixed at a mass ratio of (15~25):(85~75), and then melt-blended and extruded by a twin-screw extruder to obtain hydrolysis-resistant masterbatch. S2. Material Mixing and Drying: By mass, mix 100 parts of polyether-type thermoplastic polyurethane matrix resin, 3-5 parts of the hydrolysis-resistant masterbatch obtained in step S1, 1-2 parts of hydrophobic synergist, and 0.2-0.5 parts of processing aids evenly. Then, place the mixture in a dehumidifying drying device and dry it using a stepped heating process until the moisture content of the material is below 0.02%. S3, Melt Extrusion Casting: The material dried in step S2 is fed into a single-screw casting extruder and melted and plasticized at a low temperature of 165℃~185℃ from the feeding section to the die head. The material is then extruded through the die head to form a molten film. S4. Rapid cooling and stretching: After the molten film leaves the die head, it is immediately contacted with the first cooling roller at a temperature of 13℃~17℃ for rapid cooling to form a cast base film; then the cast base film is preheated and subjected to unidirectional stretching treatment with a ratio of 1:15~1:20 in the longitudinal direction under the preheated state. S5. Post-processing: The stretched film is heat-set at 90℃~110℃ to eliminate internal stress; then it is wound up and placed in a constant temperature environment of 45℃~55℃ for 18~30 hours to cure, thus obtaining the hydrolysis-resistant TPU film.

2. The process for preparing hydrolysis-resistant TPU film according to claim 1, characterized in that, The number average molecular weight of the polycarbodiimide mentioned in step S1 is 2000~5000, the length-to-diameter ratio of the twin-screw extruder is 48:1, and the processing temperature range is 160℃~190℃.

3. The process for preparing hydrolysis-resistant TPU film according to claim 2, characterized in that, The hydrophobic synergist mentioned in step S2 is 5000-mesh ultrafine talc powder that has undergone surface pretreatment with titanate coupling agent, and the processing aid is ethylene bis-stearamide.

4. The process for preparing hydrolysis-resistant TPU film according to claim 3, characterized in that, The stepped heating and drying process described in step S2 specifically includes: drying at 80℃ for 1-2 hours in the first stage; drying at 100℃ for 25-35 hours in the second stage; drying at 90℃ for 05-15 hours in the third stage; and the dew point temperature of the dehumidifying and drying equipment is not higher than -50℃.

5. The process for preparing hydrolysis-resistant TPU film according to claim 4, characterized in that, The temperature settings for each section of the single-screw cast extruder in step S3 are as follows: feeding section 165℃±5℃, compression section 175℃±5℃, metering section 180℃±5℃, flange and filter area 180℃±5℃, and die head 185℃±5℃.

6. The process for preparing hydrolysis-resistant TPU film according to claim 5, characterized in that, The filter screen combination of the single screw cast extruder in step S3 is a three-layer stacked structure of 100 mesh / 200 mesh / 100 mesh.

7. The process for preparing hydrolysis-resistant TPU film according to claim 6, characterized in that, The rapid cooling treatment of the cast base film in step S4 is completed on the surface of the cooling roller at 15℃±2℃, and the preheating temperature is 80℃±5℃.

8. The process for preparing hydrolysis-resistant TPU film according to claim 7, characterized in that, The duration of the heat setting process in step S5 is 15 to 25 seconds.

9. The process for preparing hydrolysis-resistant TPU film according to claim 8, characterized in that, After the heat setting treatment in step S5 and before winding, a corona treatment step is also included, wherein the power of the corona treatment is 7~9kW and the dyne value of the treated film surface is not less than 42mN / m.

10. A hydrolysis-resistant TPU film, characterized in that, Prepared by the method according to any one of claims 1 to 9.